2022
DOI: 10.3390/mi13010116
|View full text |Cite
|
Sign up to set email alerts
|

An MHD Fluid Flow over a Porous Stretching/Shrinking Sheet with Slips and Mass Transpiration

Abstract: In the present paper, an MHD three-dimensional non-Newtonian fluid flow over a porous stretching/shrinking sheet in the presence of mass transpiration and thermal radiation is examined. This problem mainly focusses on an analytical solution; graphene water is immersed in the flow of a fluid to enhance the thermal efficiency. The given non-linear PDEs are mapped into ODEs via suitable transformations, then the solution is obtained in terms of incomplete gamma function. The momentum equation is analyzed, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Patil et al 45 and Elayarani et al 46 reported the unsteady 2D nanoliquid flow containing gyrotactic micro-organisms. Vishalakshi et al 47 and Khashi’ie et al 48 evaluated the magnetized flow of HNF across a revolving plate with the Joule heating effect. According to the outcomes, an increase in the magnetic effect makes heat transmission more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al 45 and Elayarani et al 46 reported the unsteady 2D nanoliquid flow containing gyrotactic micro-organisms. Vishalakshi et al 47 and Khashi’ie et al 48 evaluated the magnetized flow of HNF across a revolving plate with the Joule heating effect. According to the outcomes, an increase in the magnetic effect makes heat transmission more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a lot of interest in the problem of MHD nanofluid boundary layer flow over a stretching/shrinking sheet [11][12][13][14][15][16][17][18]. Alias and Hafidzuddin [14] considered the problem of a magnetohydrodynamic (MHD) induced Navier slip flow over a non-linear stretching/shrinking sheet with the existence of suction.…”
Section: Introductionmentioning
confidence: 99%
“…Jan et al [ 21 ] examined the MHD boundary-layer nanofluid flow over a vertically placed stretching surface under the impacts of viscous dissipation and heat generation/absorption factor. Vishalakshi et al [ 22 ] examined the non-Newtonian three-dimensional graphene water nanofluid flow across a porous stretching/shrinking surface in the presence of thermal radiation and mass transpiration.…”
Section: Introductionmentioning
confidence: 99%